A role of oligodendrocytes in information processing - Moore, Sharlen (Nat Commun, 2020)
Myelinating oligodendrocytes enable fast propagation of action potentials along the ensheathed axons. In addition, oligodendrocytes play diverse non-canonical roles including axonal metabolic support and activity-dependent myelination. An open question remains whether myelination also contributes to information processing in addition to speeding up conduction velocity. Here, we analyze the role of myelin in auditory information processing using paradigms that are also good predictors of speech understanding in humans. We compare mice with different degrees of dysmyelination using acute multiunit recordings in the auditory cortex, in combination with behavioral readouts. We find complex alterations of neuronal responses that reflect fatigue and temporal acuity deficits. We observe partially discriminable but similar deficits in well myelinated mice in which glial cells cannot fully support axons metabolically. We suggest a model in which myelination contributes to sustained stimulus perception in temporally complex paradigms, with a role of metabolically active oligodendrocytes in cortical information processing.